"Vyhublé postuláty rozumové víry.": k Habermasově kritice Kantovy filosofie náboženství - Sirovátka, Jakub (Filosoﬁcký časopis)
In his late magnum opus, Auch eine Geschichte der Philosophie, Jürgen Habermas seeks to reconstruct what the “post-metaphysical” age lost when it abandoned metaphysics. Habermas sees a fundamental bifurcation of metaphysical thought in the eighteenth century, namely in the parting of the ways represented by David Hume and Immanuel Kant. In my paper, I will particularly focus on Habermas’s critique of Kant’s philosophy of religion. As a first step, I will present his critical conception of Kant’s practical philosophy in conjunction with his philosophy of religion, which, according to Habermas, fails in its attempt to rescue religious contents within a secular philosophy. The crucial weakness that Habermas identifies in Kant’s systematics is the demands that arise from the absolute validity of the moral law. I will then, in a second step, critically discuss this interpretation of Habermas, attempting to point out the weaknesses of his interpretation. In contrast to Habermas’s attempt, however, I am convinced that the philosophy of religion is a constitutive and plausible part of Kant’s philosophy.